Stereotypes in Families: Parents’ Gender Characters and Youngsters’ Aspirations - Sierto, Maricel E.; Navarro, Ricky J. (International Journal of Multidisciplinary: Applied Business and Education Research, 2024)
The study’s main purpose is to determine the impact of parents’ beliefs and behavior to the professional aspirations of their children. The present study specifically pursued answers to the subsequent questions: (1) What is the status of gender stereotypes in families of students at Bulacan State University-Bustos Campus?; (2) What is the percentage of parents’ gender characters toward their children? And (3) What is the impact of parents’ beliefs and behavior in their children’s professional aspirations? This study used a descriptive study that used a questionnaire to collect relevant data. The results show that (1) Even though there are parents who decide about the career path of their children, there are parents who let their children decide about their professional aspirations; (2) The key influence on the development of gender stereotyping in early life is parents' conduct towards their offspring, which is the primary influence on the development of gender role stereotyping in early life. The socialization process of children is influenced by parents providing a helpful setting within the family for them to engage in face-to-face interactions with their children; and (3) It is essential for a child to make this decision themselves. Choosing a profession helps kids become more independent. Children who are given the opportunity to make a decision that will affect their future will become more confident and reliant on themselves.